Implementasi Algoritma ID3 Pada Analisa Data Pengolahan Karet - Nuraini (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
PT. Socfindo, rubber cultivation and production is one of the main activities, where production risks play a significant role. Fluctuating rubber production and productivity are among the consequences of production risks. The production and productivity of natural rubber at Aek Pamienke PT Socfindo have experienced fluctuations from 2009 until now. There have even been instances of unmet production targets at the company. This is attributed to several production risks, such as technological usage, rainfall, pests, and diseases, resulting in a yearly decrease in total rubber processing despite consistent land area. Data mining is a process that utilizes statistical techniques, mathematics, artificial intelligence, and machine learning to extract and identify useful information and related knowledge from various large databases. The ID3 algorithm is one data mining algorithm specifically applied to decision tree techniques. By employing the classification algorithm ID3, it can assist PT. Socfindo Aek Pamienke in processing rubber processing data. In this algorithm, the selection of attributes to be processed uses information gain. In selecting attributes for object resolution within multiple data, the attributes that produce the greatest information gain must be chosen.